2014
DOI: 10.1016/j.sapharm.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Potential health implications of racial and ethnic disparities in meeting MTM eligibility criteria

Abstract: Background Previous studies have found that racial and ethnic minorities would be less likely to meet the Medicare eligibility criteria for medication therapy management (MTM) services than their non-Hispanic White counterparts. Objectives To examine whether racial and ethnic disparities in health status, health services utilization and costs, and medication utilization patterns among MTM-ineligible individuals differed from MTM-eligible individuals. Methods This study analyzed Medicare beneficiaries in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…This study's findings concerning disparities follow patterns similar to those identified in prior research, as summarized in Table . It was previously reported that according to 2006 MTM eligibility thresholds (the most restrictive since MTM implementation), the adjusted odds ratios for meeting eligibility criteria for blacks and Hispanics compared to whites were 0.36–0.60 ( P <0.05) and 0.13–0.46 ( P <0.05) respectively .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This study's findings concerning disparities follow patterns similar to those identified in prior research, as summarized in Table . It was previously reported that according to 2006 MTM eligibility thresholds (the most restrictive since MTM implementation), the adjusted odds ratios for meeting eligibility criteria for blacks and Hispanics compared to whites were 0.36–0.60 ( P <0.05) and 0.13–0.46 ( P <0.05) respectively .…”
Section: Discussionsupporting
confidence: 87%
“…To address the problem of disparities in MTM eligibility, a fourth‐stage strategy, a comprehensive approach, needs to be taken. Changing MTM eligibility criteria can only be one prong of the solution; addressing the pattern of lower utilization of prescription drugs among minorities than whites is critical …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stakeholders, however, have continued to question the value of current Medicare Part D eligibility criteria, and the Centers for Medicare and Medicaid Services is currently considering significant changes to these criteria . Further evaluation of predictors of MRPs and, subsequently, MTM eligibility criteria is warranted among both Medicare beneficiaries and other populations.…”
mentioning
confidence: 99%
“…1 These reports and other studies have demonstrated that minorities are more likely to receive poor quality of care and have poor access to preventive care, acute treatment, and chronic disease management in comparison to non-Hispanic Whites (referred to hereafter as ‘Whites’). 1-4 A recent study found that eliminating racial and ethnic disparities would have reduced $229.4 billion in direct medical costs in the United States in 2003-2006. Additionally it was found that during this period, 30.6% of direct medical expenditures for racial and ethnic minorities including non-Hispanic Blacks (referred to hereafter as ‘Blacks’) and Hispanics came from additional costs due to health inequalities.…”
Section: Introductionmentioning
confidence: 99%